Massive Myoepithelial Carcinoma Originating from the Submandibular Gland That Was Successfully Treated with Surgical Excision, Using a Part of the Lengthened Skin as a Local Flap - Hayashi, Ayato (Plast Reconstr Surg Glob Open, 2015)
Myoepithelial carcinoma is rare and mostly originates from the major salivary glands. Sometimes, it is difficult to differentiate the benign from the malignant histologically, and its clinical behavior and histological features may vary. Here, we describe the case of a 55-year-old woman who presented with a massive myoepithelial carcinoma, which hung like a temple bell from her right side of the jaw, and she refused to go to the hospital for 3 years. Based on its size and location, we initially thought that, before surgical resection, neoadjuvant therapy would be necessary to reduce the tumor volume. However, after careful evaluation of the tumor characteristics (low-grade histology with outward expansion and little invasion of the adjacent tissues) and imaging findings, we decided that excision was possible. The tumor was encapsulated and had a clear border; it weighed 10.5 kg. By setting the incision line posterior to the equatorial plane and using the lengthened skin posterior to the tumor as a large local flap for the skin defect, we successfully reconstructed the skin defect without harvesting additional flap from other areas. No additional treatment was administered because a sufficient surgical margin was maintained, pathologically. She regained her daily life without recurrence or distant metastasis for 2 years. When treating a massive tumor, careful consideration of its characteristics and location is important, and in this case, we were able to use a simpler and less invasive treatment than we initially envisioned.